2019
DOI: 10.1002/mds.27718
|View full text |Cite
|
Sign up to set email alerts
|

The A1 astrocyte paradigm: New avenues for pharmacological intervention in neurodegeneration

Abstract: We recently demonstrated that NLY01, a novel glucagon‐like peptide‐1 receptor agonist, exerts neuroprotective effects in two mouse models of PD in a glia‐dependent manner. NLY01 prevented microglia from releasing inflammatory mediators known to convert astrocytes into a neurotoxic A1 reactive subtype. Importantly, we provided evidence that this neuroprotection was not mediated by a direct action of NLY01 on neurons or astrocytes (e.g., by activating neurotrophic pathways or modulating astrocyte reactivity per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 108 publications
(214 reference statements)
3
56
0
Order By: Relevance
“…Microglia also secretes cytokines, chemokines, and different types of interferons which affect the functionality of reactive astrocytes and neurons [92,93]. To prevent microglia-dependent activation of astrocytes, several authors have used pegylated exedin4 (NLY01), an agonist of glucagon-like peptide1 (GLP1) receptor, which reduces the levels of IL-1α, TNFα, and C1q [42,43]. In the same way, some reports suggest a beneficial effect of propranolol (an antagonist of β-adrenergic receptors) in preventing microglia activation [44] (Table 1).…”
Section: Relationship Between Reactive Astrocytes and Microglia In Nementioning
confidence: 99%
“…Microglia also secretes cytokines, chemokines, and different types of interferons which affect the functionality of reactive astrocytes and neurons [92,93]. To prevent microglia-dependent activation of astrocytes, several authors have used pegylated exedin4 (NLY01), an agonist of glucagon-like peptide1 (GLP1) receptor, which reduces the levels of IL-1α, TNFα, and C1q [42,43]. In the same way, some reports suggest a beneficial effect of propranolol (an antagonist of β-adrenergic receptors) in preventing microglia activation [44] (Table 1).…”
Section: Relationship Between Reactive Astrocytes and Microglia In Nementioning
confidence: 99%
“…It was shown that A1 astrocytes fail to support neuronal survival; in contrast, they can trigger neuronal degeneration (Liddelow et al, 2017). Their increased number was demonstrated in HD as well as in other neurodegenerative diseases (Hinkle et al, 2019). However, the higher presence of A1 astrocytes specifically was not measured in TgHD minipigs.…”
Section: Discussionmentioning
confidence: 99%
“…Rationale for this prediction is supported by studies from other neurodegenerative diseases with chronic inflammation and reactive glial cell populations. Upon stressful stimuli, astrocytes become activated from a quiescent state, become reactive and undergo structural and functional changes (Ferrer, 2017 ; Hinkle et al, 2019 ). In this context, astrocytes can be classified into numerous subtypes based on morphology, activation state and anatomical location.…”
Section: Astrocyte Phenotype and Glymphaticsmentioning
confidence: 99%
“…As discussed in previous sections of the review, some astrocytes are infected by HIV and can produce and release several viral proteins such as Tat, Nef, and Rev due to integrated virus, thereby inducing an A1 phenotype and production of inflammatory factors that damage surrounding cells (Hinkle et al, 2019 ; Shijo et al, 2019 ). Thus, the A1 astrocyte phenotype likely contributes in part to the development HAND (Ances and Clifford, 2008 ).…”
Section: Astrocyte Phenotype and Glymphaticsmentioning
confidence: 99%